ELECTIONS AND THE ECONOMY OF ISLAMIC BOARDING SCHOOLS IN INDONESIA: POSITIVE AND NEGATIVE IMPACTS - Lestari, Dwi Puji; Sa’niyah, Jumrotus; Wahib, Mahasinul; Garijati Arkiang, Rochdal; Budianto, Lestari; Lesmana, Ceta Indra (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research article explores the complex relationship between electoral processes and the economic dynamics of Islamic boarding schools (pesantren) in Indonesia. Through a comprehensive analysis of the economic activities and funding sources of pesantren, this research aims to identify both the beneficial and detrimental impacts of elections on these religious institutions. The research highlights how political campaigns and promises of financial support during election periods can lead to increased investments and improvements in infrastructure within pesantren. Conversely, the research also uncovers the potential for economic instability caused by the politicization of educational funding, leading to fluctuating resources and dependency on political agendas. By examining case studies from various regions, the article provides a nuanced understanding of how electoral outcomes can influence the sustainability and economic resilience of Islamic boarding schools. The findings underscore the need for a more stable and transparent funding mechanism that ensures the financial health of pesantren, irrespective of political cycles. This research contributes to the broader discourse on the intersection of politics, education, and religion in Indonesia, offering valuable insights for policymakers, educators, and religious leaders.